2016
DOI: 10.1002/pi.5303
|View full text |Cite
|
Sign up to set email alerts
|

Graphene network enabled high speed electrical actuation of shape memory nanocomposite based on poly(vinyl acetate)

Abstract: Here strong electroactive shape memory nanocomposites were prepared by incorporating graphene nanoplatelets into poly(vinyl acetate) (PVAc) through the simple solvent mixing method. TEM and XRD revealed that well exfoliated graphene nanoplatelets formed a continuous network throughout the matrix with a large amount of interconnectedness. Dynamic mechanical analysis showed that the inclusion of graphene significantly improves both glassy and rubbery moduli of the matrix. Furthermore, the prepared nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…In addition, Figure exhibits that the embedding of graphene nanoplatelets into the fibrous structures did not noticeably change the morphology of fibers, and the mean diameter of fibers slightly reduced in the presence of nanofillers. We have previously established that the incorporation of graphene nanoplatelets into the PLA, PVAc, and PLA/PVAc matrices leads to a significant increase in their electrical conductivity. Therefore, the electrical conductivity of polymer solutions can be increased in the presence of graphene and, as a result, net charge density on the surface of jet increases during the electrospinning process, which can account for the decrease in diameter of the nanofibers containing graphene …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Figure exhibits that the embedding of graphene nanoplatelets into the fibrous structures did not noticeably change the morphology of fibers, and the mean diameter of fibers slightly reduced in the presence of nanofillers. We have previously established that the incorporation of graphene nanoplatelets into the PLA, PVAc, and PLA/PVAc matrices leads to a significant increase in their electrical conductivity. Therefore, the electrical conductivity of polymer solutions can be increased in the presence of graphene and, as a result, net charge density on the surface of jet increases during the electrospinning process, which can account for the decrease in diameter of the nanofibers containing graphene …”
Section: Resultsmentioning
confidence: 99%
“…Our recent works revealed that the inclusion of graphene nanoplatelets into SMPs can significantly improve the SM properties . Therefore, effect of the graphene loading into the each phase of composite mats on the thermomechanical and subsequently triple‐SM behavior of samples is also evaluated in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shape memory polymers (SMPs) belong to smart materials which can ‘memorize’ their initial shape and restore the initial shape from other temporary shapes as a response to external stimuli such as temperature, moisture, solution, electrical current, magnetic fields, pH and light etc. SMPs bear many advantages over traditional shape memory alloys and ceramics; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SMPs can be divided into two main categories. One is polymer networks, including covalent crosslinked or physical crosslinked semicrystalline or amorphous copolymers; the other is polymer blends and composites . Because the synthesis of SMPs may be difficult, physical blending of polymers is a convenient and effective way to prepare shape memory composites and has potential in industrial applications.…”
Section: Introductionmentioning
confidence: 99%